2020
DOI: 10.1002/esp.5021
|View full text |Cite
|
Sign up to set email alerts
|

Hillslope sediment fence catch efficiencies and particle sorting for post‐fire rain storms

Abstract: Sediment fences are often used to monitor hillslope erosion, but these can underestimate sediment yields due to overtopping of runoff and associated sediment. We modified four sediment fences to collect and measure the runoff and sediment that overtopped the fence in addition to the sediment deposited behind the fence. Specific objectives were to: (1) determine the catch efficiency of sediment fences measuring post‐fire hillslope erosion; (2) assess particle sorting of sand, silt/clay, and organic matter from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…In the dynamic post‐fire environment obtaining accurate measurements of runoff and sediment transport is extremely difficult, and the values presented here have fairly high uncertainty. Hillslope runoff measurements are affected by the accuracy of the weir equation and stage readings from cameras, which exclude any water that ponds or infiltrates inside the sediment fence (e.g., Wilson et al, 2020). Streamflow and in‐stream sediment yields are affected by the accuracy of the rating curves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the dynamic post‐fire environment obtaining accurate measurements of runoff and sediment transport is extremely difficult, and the values presented here have fairly high uncertainty. Hillslope runoff measurements are affected by the accuracy of the weir equation and stage readings from cameras, which exclude any water that ponds or infiltrates inside the sediment fence (e.g., Wilson et al, 2020). Streamflow and in‐stream sediment yields are affected by the accuracy of the rating curves.…”
Section: Discussionmentioning
confidence: 99%
“…In summer 2014 two additional sediment fences and one additional rain gauge were installed within the headwaters of Skin Gulch. These two new sediment fences and two existing sediment fences in the headwaters of Hill Gulch were instrumented to continuously monitor runoff and the amount of sediment that overtopped the sediment fence (Figures 1 and 2; Wilson et al, 2020). Contributing areas for the 31 hillslope monitoring sites ranged from 0.1 to 2.8 ha (truex¯ = 0.5 ha) with average slope of 5–33°, and elevations from 1780–2670 m.…”
Section: Methodsmentioning
confidence: 99%
“…They also found that 86 % of P was exported in particulate form. As P is preferentially transported associated to sediment particles (Ferreira et al, 2016a;Serpa et al, 2020), the use of sediment fences, which capture mostly particulate fractions (Robichaud and Brown, 2002;Wilson et al, 2021) may be more effective at retaining P than runoff plots. On the other hand, runoff tanks have a limited storage capacity and other limitations associated to sample homogenization (Bagarello and Ferro, 1998).…”
Section: Organic Matter N and P Exports With Eroded Sedimentsmentioning
confidence: 99%
“…Consequently, in soils where matrix flow dominates, K fs should be measured with tension infiltrometers or simulated rainfall, whereas in locations where macropores dominate, ponded head methods are preferable (Ebel, 2019). Wilson et al (2020) focused on best practices for measuring sediment production. They show how particle sorting occurs after sediment fences are overtopped and provide practical suggestions to appropriately size sediment fences by modeling runoff.…”
Section: Special Issue Advancesmentioning
confidence: 99%